Obtaining new brewing yeasts using regional Chilean wine yeasts through an adaptive evolution program - Contreras, Ángela; Villalobos-Cid, Manuel; Valdés, Cristian; Villarroel, Carlos A.; Castro, Felipe; Farías, Ignacio; Lorca, Gustavo (Frontiers in Microbiology, 2025)
Beer consumption has increased worldwide, positioning it as the most consumed alcoholic beverage on the market. Saccharomyces cerevisiae brewing yeasts have specific genetic characteristics that allow them to survive in malt wort using maltose and maltotriose as the principal carbon source. However, metabolizing these sugars is challenging for non-brewery Saccharomyces strains under typical brewing conditions, which involve high osmotic stress and low temperatures. These conditions restrict beer producers to a limited range of yeast strains, increasing their cost and contributing to beer flavors uniformity. Here, we performed an adaptive evolution process to improve the fermentative capacities of S. cerevisiae winemaking yeasts isolated from Chilean vineyards to allow their use in brewing. Initially, we screened 50 strains of viticultural origin collected from different areas of Chile. Five strains were selected based on their fermentative capacities, sugar consumption, flavor and aroma, after which were subjected to an adaptive evolution process of 600 generations. We obtained an evolved strain that was able to consume maltose and maltotriose, growing in very high gravity wort (29°P) and at low temperatures (18°C) without shaking. We used DNA sequencing to examine genome changes that could explain the superior beermaking phenotype of the evolved strain. We found that the evolved strain completely lost a parental genome and showed aneuploidies, resulting in gene copy number variations. Interestingly, duplications in genes related to maltose metabolism (IMA1, MAL13 and MAL11) were observed. Moreover, we also found 160 genes that lost a copy in the evolved strain, of which three showed complete loss: FLO5, PAU8, and SEO1. These genes are related to wine yeast survival under the stress conditions of grape must (lower pH, higher glucose and ethanol concentration than wort). Our results show a successful application of high stress levels to evolve regional winemaking strains to improve their fermentative traits for the brewing process. Applying this method will make it possible to obtain yeasts that can carry out alcoholic fermentation in wort without having to buy unique strains called “brewing yeasts.”